Distance Learning: GeoGebra-Learning Videos to Improving Mathematical Communication Ability - Nasrullah, Anton; Mubarika, Melinda Putri; Umalihayati (International Journal of Emerging Technologies in Learning (iJET), 2023)
This study aims to use the GeoGebra application as a learning aid and ascertain the efficacy of learning videos in calculus education. Using a mathematical communication test, the research employs a quantitative approach and a quasi-experimental technique to acquire data. This study’s sample is a second-year student enrolled at a Serang-Banten university. The sample is comprised of two divisions. One class is utilized for the control group of 25 pupils and another for the experimental group of 30. In the control group, students were only taught in an online learning environment using the Zoom Meet application without explaining GeoGebra-learning videos. The findings show differences in the increase in mathematical communication skills of students who study online using GeoGe-bra-learning videos (the experimental group) and those who get online learning without using GeoGebra- learning videos (the control group). Thus, GeoGebra-learning videos are a learning support tool that can improve students’ mathematical communication skills.